2010
DOI: 10.1002/jrs.2600
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Raman mapping study of the microheterogeneity in 0.67PbMg1/3 Nb2/3O3‐0.33PbTiO3 single crystal

Abstract: Polarized micro-Raman spectroscopy was carried out on the (001) face of a 0.67PbMg 1/3 Nb 2/3 O 3 -33%PbTiO 3 (PMN-33%PT) single crystal. The Raman images revealed the spatial variations of the intensity of the Raman bands, suggesting that the structure in the PMN-33%PT single crystal varied from one micro-area to another. When changing the polarization direction of the incident light with respect to the selected crystalline axes, the intensities of the Raman modes varied periodically. According to the Raman s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
(76 reference statements)
3
9
0
Order By: Relevance
“…In fact, the angular dependence recorded in the dark and light areas here are also quite analogous to that of "G microregions" and "R microregions", respectively, discovered in PMN-0.33PT single crystals by authors of the Ref. 24 and then also reinvestigated in the temperature study of Ref. 30.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…In fact, the angular dependence recorded in the dark and light areas here are also quite analogous to that of "G microregions" and "R microregions", respectively, discovered in PMN-0.33PT single crystals by authors of the Ref. 24 and then also reinvestigated in the temperature study of Ref. 30.…”
supporting
confidence: 81%
“…We used the latter ratio to map the stripes and observed that in contrast to results of Ref. 24, in our sample the so-obtained relative intensity map reveals clear, about 100-micron sized stripes, which clearly match the stripes observed optically (Fig. 3b).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Heterophases in relaxor ferroelectrics lead to the misfit stress of lattice and consequently allow polarization heterogeneity for accommodating the stress. , The connections between polarizataion and structure were studied on the same region of Figure b by in situ micro-Raman imaging. Raman spectroscopy has a high sensitivity to the spatial phase variation by analyzing the soft-mode. ,, Under the same ambient pressure and temperature, the phonon frequency shift is mainly attributed to the intrinsic phase difference and the internal stress inhomogeneity. , Phonon frequency mappings around 55, 80, and 585 cm –1 in Figure f–h, respectively, clearly show a larger frequency on the left side, associating with the ribbon-shaped domain configuration, while the irregular domain area corresponds to the smaller frequency values. Similarly, Hlinka et al reported a macroscopic lamellar structure in PMN-0.32PT by polarized Raman spectroscopy, indicating an array of “morphotropic” interphase boundaries between R-like and T-like areas.…”
Section: Resultsmentioning
confidence: 97%
“…Phase instability and transverse phonon localization are the main causes for the emergence of metastable monoclinic (M) phase bridging rhombohedral (R) and tetragonal (T) symmetries. , Intermediate M-symmetry (M a , M b , and M c ) groups are believed to balance the accommodated strain and favor the multidirectional polarization states at MPB. , The as-grown PMN-based relaxor ferroelectric crystal has a rhombohedral-like (R-like) M a (space group Cm ) and tetragonal-like (T-like) M c (space group Pm ) phases coexisting at room temperature, presenting an adjacent laminar domain structure. ,− It should be noted that exploring Pb-based ferroelectric performances requires consideration of the synergistic contributions from the lattice symmetry, polar order, and internal energy. Therefore, it is necessary to explore the spatial relationships between the structure, internal energy, and polarization disorder in Pb-based relaxor ferroelectrics with MPB composition, and to further strengthen the understanding of the structure-related piezoelectric contributions.…”
Section: Introductionmentioning
confidence: 99%